Influence of New Public Management Philosophy On Risk Management, Fraud and Corruption Control and Internal Audit: Evidence from an Australian Public Sector Organization - Anup Chowdhury; Nikhil Chandra Shil (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: This study will explore how private sector financial management technologies (specifically, risk management system, fraud and corruption control system and internal audit) become embedded in a selected public sector organisation. Motivation: The motivation for this study is to explore how private sector financial management control tools contributed to and shaped new organisational culture within the public sector organisation. Idea: The idea was generated from the philosophy of New Public Management which was based on the premise that using the private sector tools, the public sector would be efficient and at the same time effectiveness would be improved (Chowdhury and Shil, 2017). Data: Qualitative research approach was adopted and data was collected in the case study tradition. Twenty top, mid and junior level executives from a selected Government Department in the Australian Capital Territory were interviewed (Chowdhury and Shil, 2016). Tools: The main data sources were interviews and archival official documents. Another tool used was direct observation which helped researchers to support the archival documents and interview data. Data were analyzed using the approach provided by Miles and Huberman (1994). Findings: Findings of the study revealed that strategic risk management is a part of the business planning life cycle of the researched Department and business units review their strategic risks as part of their business planning process. In the Department it is evident that fraud and corruption control system is a part of their cultural environment. The Department has established an independent Internal Audit and Review Unit, who provides service to management to meet all prescribed statutory responsibilities within a performance improvement environment. Contribution: The findings of the present study are expected to increase our understanding about the private sector control devices used in a public sector context and this study will be of value to the academic researchers and practitioners. The study may be useful to the policy makers also who are engaged in formulating new public sector policies. Moreover, the findings reported on this study would be useful to the public sector managers in their day to day decision-making process.
Keywords: D73; G32; H83; M48; 650; new public management; risk management; fraud and corruption control; internal audit; public sector; Australia